Dyspepsia in England and Scotland. - Jones, R; Lydeard, SE; Hobbs, F; Kenkre, J; Williams, E; Jones, S; Repper, J; Caldow, J; Dunwoodie, WM; Bottomley, J (1990)
A validated postal questionnaire has been used to establish the prevalence of dyspeptic symptoms in five geographical locations from the south coast of England to the north of Scotland. The six month period prevalence of dyspepsia in the 7428 respondents to the questionnaire is 41% and equal between the sexes, with similar prevalence rates in the centres studied. There is considerable overlap between upper abdominal symptoms and symptoms of heartburn; 56% of patients with dyspepsia experience both groups of symptoms. Symptom frequency falls progressively with age in men and women, but the proportion of people seeking medical advice for dyspepsia rises with age. One quarter of the dyspeptic patients studied have consulted a general practitioner about their symptoms. This study suggests that the prevalence of dyspepsia in the community has changed little over the last 30 years, despite evidence that the frequency of peptic ulcer disease is falling. Symptom prevalence is unrelated to social class, but this factor is associated with consultation behaviour, the consultation rate rising from 17% in social class 1 to 29% in social class 4. The use of investigations--barium meal and endoscopy--is similarly related to social class; the lowest rate for ulcer diagnosis (4.7%) is found in social class 1 and the highest (17.1%) in social class 5.